Aerial and detritus production of the cordgrass Spartina densiflora in a southwestern Atlantic salt marsh - Vera, Federico (2009)
We used a nondestructive method to estimate aerial and detritus productivity of the cordgrass Spartina densiflora Brongn. and evaluated the relative contribution of newly emerged and preexisting tillers to net aerial biomass and detritus production, the relative contribution of tiller detachment and leaf shedding to detritus production, and the incidence of crab (Neohelice (Chasmagnathus) granulata (Dana, 1851)), herbivory in relation to tiller age and its implications for tiller survival. Estimates of aerial and detritus productivity varied between 706.72 (SD = 153.38) and 786.15 (SD = 162.75) g·m–2·year–1 and between 1054.23 (SD = 224.49) and 1223.17 (SD = 246.84) g·m–2·year–1, respectively. These estimates of aerial production are far below the higher productivity estimates known for species of the genus Spartina but within the range of values obtained with nondestructive methods (i.e., 300–1500 g·m–2·year–1). Detachment of standing-dead tillers and leaf shedding contributed virtually in equal quantities to detritus production (i.e., 52% and 48% of the total detritus biomass, respectively). On the other hand, net aerial biomass production was highly dependent on tiller recruitment, with 67% of total biomass production contributed by the growth of tillers that emerged during the course of the study. However, crabs seem to graze on tillers irrespective of their age. Such nonselective crab grazing on tillers of different age together with the long tiller survival after crab grazing (often more than a year) suggests that crabs do not ostensibly affect S. densiflora production.